(untitled) (Research, Society and Development, 2022)
In face of the COVID-19 pandemic scenario, a mobilisation was initiated in the scientific community to understand the new pathogen. The role of health surveillance in the systematic collection of information relevant to the health of populations is highlighted. This is a cross-sectional, descriptive study with a quantitative approach, considering variables present in notifications and data obtained in telemonitoring, with the aim of describing the epidemiological profile of reported cases of COVID-19 in 2020, in the city of Piraquara, Paraná, Brazil. The number of notifications considered in this study was 5,238, with 92.82% detected by RT-PCR and 7.18% by rapid and serological tests. There was a considerable record of cases in December (n=1487) and a higher occurrence among females (52.48%). The age group with the highest number of cases was 30 - 39 years old (23.16%). The most reported comorbidities included systemic arterial hypertension (n=168), diabetes mellitus (n=96) and lung diseases, while the most frequently reported signs and symptoms were headache (n=1324), myalgia (n=1036), and cough (n=999). Those recovered made up 97.29% of all cases. The coverage rate of telemonitoring was high, which allowed the elaboration of the epidemiological profile, revealing the path of the pathology in the city. Data analysis shows that COVID-19 was more prevalent among females, among young adults and caused more deaths among males, especially the elderly.